Análise do efeito sistêmico da LLLT na morfologia das glândulas tireóide e sublingual : estudo em coelhos - Silveira, Vinícius Salim (2016)
This study is the result of a project that aimed to assess the systemic effects of low-level laser therapy (LLLT) on the morphology of the thyroid and sublingual glands when used as adjuvant therapy for peri-implant bone healing in the rabbit mandible. For the present study, 32 clinically healthy male New Zealand rabbits (Oryctolagus cuniculus) weighing 3 to 4 kg each were divided into four groups of eight animals each, one control group (CI, nonirradiated animals) and three experimental groups that received LLLT (group EI = 5 J/cm2 per spot; group EII = 2.5 J/cm2 per spot; and group EIII = 10 J/cm2 per spot). Animals in all experimental groups underwent seven treatment sessions with irradiation applied in two spots per session, resulting in total energy densities of 70 J/cm2, 35 J/cm2, and 140 J/cm2, respectively, in groups EI, EII, and EIII. The mandibular left incisor was surgically extracted in all animals, and an osseointegrated implant was placed immediately afterward. Control animals underwent sham irradiation following the same protocol used for irradiated animals, but with the laser device left unpowered. The experimental groups were irradiated with an aluminum-gallium-arsenide (AlGaAs) laser diode (Thera Lase®) at a wavelength of 830 nm (infrared) for spot irradiation, 50mW output power, in continuous wave mode every 48 hours over a 13-day period. LLLT began in the immediate postoperative period. All animals were euthanized 45 days after the experiment. There was no histomorphometric change in any of the groups, demonstrating that LLLT has no systemic effects that can lead to morphological changes in the thyroid and sublingual glands when used to stimulate peri-implant bone healing in the rabbit mandible.